The Development of Restricted Languages in Contemporary Sinhala with Social and Technological Influences - Ariyawansa, Dilini (International Journal of Language and Literary Studies, 2025)
British linguist J.R. Firth introduced the term 'restricted language' to refer to linguistic systems designed for specific tasks or contexts. In this context, various adaptations of the Sinhala language utilized in specialized environments can be identified as restricted forms. These adaptations often feature distinct vocabulary tailored to particular domains. For example, traditional agricultural practices, such as threshing, employ specific terminology, while the fishing community has developed a unique lexicon pertinent to their industry. Additionally, K. N. O. Dharmadasa has observed the emergence of new restricted forms in Sinhala, particularly evident in the language used in news headlines and text messaging. This study investigates the influence of recent societal developments on the emergence and characteristics of new restricted forms of the Sinhala language. In addition to analyzing websites, an exploration of social media platforms was conducted to capture the latest trends in language usage. It was observed that specific vocabulary related to epidemic and pandemic situations, as well as the headlines on gossip websites, YouTube titles and thumbnails, social media interactions, and strategies for online income generation, have begun to emerge. These elements can be classified as restricted forms of Sinhala language. Consequently, this study provides evidence of the evolving nature of restricted language forms in response to contemporary circumstances within the speaking community.